Management criteria for Ficus insipida Willd. (Moraceae) in Amazonian white-water floodplain forests defined by tree-ring analysis - Schöngart, Jochen; Wittmann, Florian Karl; Worbes, Martin; Piedade, Maria Teresa Fernandez; Krambeck, Hans Jürgen; Junk, Wolfgang Johannes (Annals of Forest Science, 2007)
Ficus insipida Willd. (Moraceae) is a fast growing tree species of early successional stages in the Amazonian nutrient-rich white-water floodplains (várzea). The species is one of the most economically important low-density wood species in the community-based forest management project in the Mamirauá Sustainable Development Reserve (MSDR) in Central Amazonia, where timber species are managed using a polycyclic selection system with a minimum logging diameter (MLD) of 50 cm and a cutting cycle of 25 years. In this study we analyze the floristic composition, stand structure and forest regeneration of a natural 20 year-old stand at an early successional stage and we model tree growth of diameter, height and volume of F. inspida based on tree-ring analysis to define management criteria. The volume growth model indicates that the preferred period for logging should be at a tree age of 17 years when the current annual volume increment peaks. This age corresponds to a diameter of 55 cm, which would be an appropriate MLD. © INRA, EDP Sciences, 2007.
Keywords: Diameter; Dicotyledon; Floodplain; Forest Management; Growth Modeling; Logging (timber); Regeneration; Timber; Tree Ring; Wild Population; Wood; Amazonia; South America; Ficus (angiosperm); Ficus Insipida; Moraceae